2018
DOI: 10.1038/s41537-018-0063-7
|View full text |Cite
|
Sign up to set email alerts
|

Diverse definitions of the early course of schizophrenia—a targeted literature review

Abstract: Schizophrenia is a debilitating psychiatric disorder and patients experience significant comorbidity, especially cognitive and psychosocial deficits, already at the onset of disease. Previous research suggests that treatment during the earlier stages of disease reduces disease burden, and that a longer time of untreated psychosis has a negative impact on treatment outcomes. A targeted literature review was conducted to gain insight into the definitions currently used to describe patients with a recent diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 180 publications
0
32
0
3
Order By: Relevance
“…To strengthen the effectiveness of interventions, a deeper scientific effort is needed to properly identify and characterize the early phase of the disease. The lack of standardised definitions of early SCH allows for considerable variation of patient groups between studies 2 . The term first-episode psychosis (FEP) is typically used to refer to an individual who has presented, been evaluated, and received treatment for the first abrupt or insidious onset of a psychotic episode associated with an SCH spectrum diagnosis 3 .…”
Section: Metabolomics Approach Revealed Robust Changes In Amino Acid mentioning
confidence: 99%
“…To strengthen the effectiveness of interventions, a deeper scientific effort is needed to properly identify and characterize the early phase of the disease. The lack of standardised definitions of early SCH allows for considerable variation of patient groups between studies 2 . The term first-episode psychosis (FEP) is typically used to refer to an individual who has presented, been evaluated, and received treatment for the first abrupt or insidious onset of a psychotic episode associated with an SCH spectrum diagnosis 3 .…”
Section: Metabolomics Approach Revealed Robust Changes In Amino Acid mentioning
confidence: 99%
“…Participants (N = 137) were 72 individuals in the early stage of a psychotic disorder (EP) and 65 healthy control individuals (HC) recruited between May 2013 and September 2017 for a prospective 2-year longitudinal study on hippocampal structure and function in the early stages of psychosis (Table 1). To specifically target early pathology 35 , the majority of early psychosis participants were recruited during the initial months of illness (i.e., the average duration of psychosis was <7 months). Early psychosis participants were recruited from the inpatient and outpatient clinics of the Vanderbilt University Medical Center Psychiatric Hospital and healthy controls were recruited from the surrounding community through advertisements.…”
Section: Participantsmentioning
confidence: 99%
“…This study has several limitations: first, the small sample size could have limited the statistical power of the analyses and the possibility to perform further, potentially interesting analyses, such as the comparison between type of intervention (IPT and CACR) in early course and chronic patients; second, the possibility to generalize the results may be restricted by the specific sample recruited for the study, including patients followed in the Italian psychiatric rehabilitation services; third, the original study was not explicitly designed with the purpose of comparing the differences of the effects of CR between patients with schizophrenia in their early course of illness and chronic patients; fourth, being an exploratory study, a correction for multiple comparisons was not used, in order to avoid the possibility of missing potentially interesting results, to be further analyzed in future studies; fifth, the cutoff for early course patients, although not one of the strictest among those proposed in literature (36), did not allow the identification of two groups of identical size, thus further limiting the statistical approach. Nevertheless, in a recent review about the diverse definition of the early course of schizophrenia, the authors suggested that disease duration of <5 years encompasses the previous definition of the critical period for early intervention (36).…”
Section: Discussionmentioning
confidence: 99%
“…This cutoff of 5 years was chosen according to literature on early course definition in schizophrenia and CR in early course patients with schizophrenia (19, 36).…”
Section: Methodsmentioning
confidence: 99%